Inhibition of CYP2C9 by selective serotonin reuptake inhibitors in vitro: studies of phenytoin p-hydroxylation - Schmider, Jürgen (1997)
Aims Inhibition of cytochrome P450 (CYP) activity by selective serotonin reuptake inhibitors (SSRIs) has frequently been reported with regard to pathways mediated by CYP2D6, CYP3A4/5, and CYP1A2. Little data exist on the capability of SSRIs to inhibit CYP2C9. Methods We investigated the effect of SSRIs on p-hydroxylation of phenytoin (PPH), an established index reaction reflecting CYP2C9 activity, in an in vitro assay using liver tissue from six different human donors. Results In control incubations (without inhibitor), 5-( p-hydroxy-phenyl)-5phenylhydantoin (HPPH) formation rates were: V(max) 0.023 nmol min(−1) mg(−1); K(m) 14.3 μm. Average inhibition constants (K(i) ) differed significantly among the SSRIs, with fluvoxamine having the lowest K(i) (6 μm ) followed by R-fluoxetine (13 μm ), norfluoxetine (17 μm ), RS-fluoxetine (19 μm ), sertraline (33 μm ), paroxetine (35 μm ), S-fluoxetine (62 μm ), and desmethylsertraline (66 μm ). Thus, assuming comparable molar concentrations at the site of inhibition, fluvoxamine can be expected to have the highest probability of interfering with the metabolism of CYP2C9 substrates. S-fluoxetine is on average a 5 fold weaker CYP2C9 inhibitor than either R-fluoxetine or the racemic mixture. Conclusions These findings are consistent with published case reports describing SSRI-related increments in plasma phenytoin levels. Because phenytoin has a narrow therapeutic index, plasma levels should be closely monitored when SSRIs are coadministered.